Report: Sixth meeting of the African Elephant Specialist Group - Leo Niskanen (Pachyderm)
Reviews the sixth meeting of the AfESG,which was attended by 34 of the 48 members, held December 4-8, 2003 at Mokuti Lodge on the edge of Etosha NP in northern Namibia. Several papers presented at meeting are in this issue of Pachyderm and others will appear in following issues. Five topics covered during the meetings are discuss: multiple species of African elephant, listing of the African elephant in the IUCN Red List, wild sourcing of African elephants for captivity, effect a stategy for assessing the future of the African elephant, and review approach to managing local overpopulation. The participants reviewed the discussion focused on multiple species of the African elephant which took place during of the fifth members meeting in Shaba and the text on the website resulting in a revised text now on the website: http://iucn.org/afesg. A temporary taskforce for was struck to look at how the African elephant fits into the IUCN Red List version 3.1 . Discussion on the wild sourcing of Africa elephants for captivity led to a decision that no direct benefit to en situ conservation occurs when this is done, and AfESG does not endorse this activity - a statement to this effect in now on the website. An interesting component of this meeting involved strategic thinking focused on a scenario planning approach to the conservation of African elephant on a continental basis - further analysis via subregioanl workshops focused on this analysis will be forthcoming. The problem of local overpopulations is one for which alternatives need to be assesed and to this end a Local Population Task Force will be struck and begin working in May 2004.